Dampak Kepemimpinan Strategis terhadap Keberhasilan Strategi Bisnis dengan Turbulensi Lingkungan sebagai Variabel Moderasi - Sikki, Nurhaeni; Nuraeni HR, Leni; Putri, Rezki Utami; Rifa, Novita Purnama (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the effect of strategic leadership on business strategy success, with environmental turbulence as a moderating variable. In an increasingly dynamic and competitive business environment, organizations must adapt quickly to changes in technology, market conditions, and competition. Strategic leadership plays a critical role in ensuring that organizational strategies are effectively formulated and implemented to achieve sustainable competitive advantage. This research adopts a quantitative approach with an explanatory design. Data were collected through structured questionnaires distributed to managers, supervisors, and employees involved in strategic decision-making. The sampling technique used was purposive sampling, with respondents selected based on specific criteria, including a minimum of one year of work experience and involvement in strategy implementation. Data analysis was conducted using Moderated Regression Analysis (MRA) to test both direct and interaction effects. The results indicate that strategic leadership has a significant positive effect on business strategy success. Additionally, environmental turbulence significantly moderates this relationship, strengthening the influence of strategic leadership under conditions of high uncertainty and rapid change. This finding suggests that the role of strategic leadership becomes more critical as environmental complexity increases. In conclusion, organizations are encouraged to develop adaptive and responsive leadership capabilities to effectively navigate turbulent environments and enhance strategic outcomes. This study contributes to the literature by highlighting the importance of environmental turbulence in shaping the effectiveness of strategic leadership.